2014
DOI: 10.1103/physrevlett.112.117602
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Bicomponent Molecular Monolayers: Adsorption Height Changes and Their Consequences

Abstract: Codeposition of two molecular species [CuPc (donor) and PFP (acceptor)] on noble metal (111) surfaces leads to the self-assembly of an ordered mixed layer with maximized donor-acceptor contact area. The main driving force behind this arrangement is assumed to be the intermolecular C-F ··· H-C hydrogen-bond interactions. Such interactions would be maximized for a coplanar molecular arrangement. However, precise measurement of molecule-substrate distances in the molecular mixture reveals significantly larger ads… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 37 publications
(39 reference statements)
5
47
0
Order By: Relevance
“…For NTCDA + CuPc the adsorption height changes are the smallest, but with ≈0.05Å still significant, apparently due to the fact that the difference of the adsorption heights in the respective homomolecular phases is small. Note that the height alignment of both molecules is -at first sight -the contrary of what was observed for a very similar heteromolecular adsorbate system: Goiri et al observed an increase of the adsorption height difference when CuPc is mixed with perfluoropentacene (PFP) [39]. However, in contrast to all the systems investigated in our study, here the acceptor molecule PFP is initially (i.e., in its homomolecular phase) located at a larger distance to the surface than the donor molecule CuPc.…”
Section: Vertical Structurementioning
confidence: 68%
See 1 more Smart Citation
“…For NTCDA + CuPc the adsorption height changes are the smallest, but with ≈0.05Å still significant, apparently due to the fact that the difference of the adsorption heights in the respective homomolecular phases is small. Note that the height alignment of both molecules is -at first sight -the contrary of what was observed for a very similar heteromolecular adsorbate system: Goiri et al observed an increase of the adsorption height difference when CuPc is mixed with perfluoropentacene (PFP) [39]. However, in contrast to all the systems investigated in our study, here the acceptor molecule PFP is initially (i.e., in its homomolecular phase) located at a larger distance to the surface than the donor molecule CuPc.…”
Section: Vertical Structurementioning
confidence: 68%
“…Due to their relevance for devices, mixed films containing one charge-donating and one chargeaccepting species are of special interest. Several groups have started to investigate such systems, and, for obvious reasons, prototypical molecules, the homomolecular adsorption of which is well understood, were combined to heteromolecular adsorbate systems in first instance [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Our group has concentrated on the molecules named above, PTCDA, NTCDA and MePcs, and investigated both laterally mixed structures (i.e., two molecules in different stoichiometries combined in one layer) [40][41][42] and heteromolecular stacks of layers whereby each individual layer contains only one species [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…19,21,34,35 However, as recently shown, those changes may be dominated (compensated or even reversed) by changes in the work function, which for the blends corresponds in a good approximation to a weighted average of the work functions associated with layers of each of the molecules separately. 19,20 The work function of the 1:2 blend on Cu(111) is slightly lower than that of F 16 To confirm this assumption, valence band photoemission and NEXAFS spectra were measured for the blend. Figure 3a shows valence band spectra of the 1:2 blend grown by sequential deposition of 0.5 ML of PEN followed by 0.5 ML of F 16 CuPc (note that due to the different molecular sizes a 1:1 ratio in surface area coverage corresponds to a 1:2 stoichiometry), although equivalent results can be obtained by co-depositing the two molecular species.…”
Section: Articlementioning
confidence: 96%
“…In particular, experimental studies on the molecule-substrate bonding distances, which provide the points of reference for adequate theoretical modeling, are rare-in contrast to the numerous experimental studies on single molecule adsorption [15,16] and 2D molecular layers based on intermolecular interactions different than metal coordination [17][18][19][20][21][22][23][24][25][26]. However, these data are crucial for understanding molecule-substrate interactions and of interest for determining possible distortions from the planar geometry of surface-confined 2D MOFs.…”
Section: Introductionmentioning
confidence: 99%